STEM critical thinking assessment untuk pengukuran kemampuan berpikir kritis mahasiswa pada mata kuliah Kimia Otomotif - Dwi Septiana Sari; Yeni Widiyawati; Indri Nurwahidah; Toni Setiawan (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking is one of the HOTS areas that students must master. Students can use these skills to solve contextual problems when studying automotive chemistry. The development of STEM-based instruments to measure STEM critical thinking is still rare. This study aims to develop a STEM-critical thinking assessment to measure students' critical thinking skills in the Automotive Chemistry course. This type of research is R&D which modifies the Borg and Gall model. Instruments developed in the form of questions and reasoning to determine students' critical thinking skills. The questions developed cover the dimensions of critical thinking skills, including argument analysis; answering questions for assignment determination; consider the credibility of the source; monitoring and calculating results; draw conclusions; make and evaluate decisions; define and evaluate terms; identify assumptions; and determine the action. The validation results from evaluators, learning experts and chemistry teachers show that the instrument is valid and can be used to measure students' critical thinking skills in automotive chemistry courses.